Association of performance in a stair-climbing test with complications and survival after lung cancer resection in the video-assisted thoracoscopic surgery era: population-based outcomes. Issue 3 (16th August 2021) - Helminen, Olli; Valo, Johanna; Andersen, Heidi; Söderström, Johan; Sihvo, Eero
Introduction: With a population-based cohort in the video-assisted thoracoscopic surgery (VATS) era, we aimed to evaluate the value of the stair-climbing test (SCT) on short- and long-term outcomes of lung cancer surgery. Methods: All patients operated due to primary lung cancer in Central Finland and Ostrobothnia from 2013 to June 2020 were included. For the analysis, clinical variables including the outcome of SCT and cause-specific mortality were available. Short- and long-term outcomes were compared between <11 m (n=66) and >12 m SCT (n=217) groups. Results: Patients with poor performance (<11 m) had more comorbidities and worse lung function but did not differ in tumour stage or treatment. No differences between groups were observed in major morbidity rate (10.6% versus 11.1%, p=0.918) or median hospital stay (5 (IQR 4–7) versus 4 (IQR 3–7), p=0.179). At 1-year, fewer patients were alive and living at home in the climbing <11 m group (81.3%) compared to the >12 m group (94.2%), p=0.002. No difference was observed in cancer-specific 5-year survival. Non-cancer-specific survival (62.9% versus 83.1%, p<0.001) and overall survival (49.9% versus 70.0%, p<0.001) were worse in the <11 m group. After adjustment for confounding factors, SCT remained as a significant predictor for non-cancer-specific (HR 4.28; 95% CI 2.10–8.73) and overall mortality (HR 2.38; 95% CI 1.43–3.98). Conclusions: With SCT-based exercise testing, VATS can be performed safely, with a similar major morbidity rate in the poor performance group (<11 m) compared to >12 m group. Poor exercise performance increases non-cancer-specific mortality. Being a major predictor of survival, exercise capacity should be included in prognostic models. According to stair-climbing-based testing, VATS surgery is safe, with similar major morbidity rates as in those with better exercise capacity. However, patients with poorer exercise capacity have significantly increased non-cancer-specific mortality. https://bit.ly/3aLB76w